2016
DOI: 10.1080/09286586.2016.1193618
|View full text |Cite
|
Sign up to set email alerts
|

Ten Emerging Trends in the Epidemiology of Diabetic Retinopathy

Abstract: The ten trends we observed in the current review may guide planning of public healthcare strategies for the management of DR and prevention of blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 100 publications
0
91
0
4
Order By: Relevance
“…The search was constructed with the help of an Information Specialist. This search strategy was expanded by examining reference lists of all included articles, as well as published review articles of diabetes in New Zealand, and global review articles of DR and DM …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search was constructed with the help of an Information Specialist. This search strategy was expanded by examining reference lists of all included articles, as well as published review articles of diabetes in New Zealand, and global review articles of DR and DM …”
Section: Methodsmentioning
confidence: 99%
“…This search strategy was expanded by examining reference lists of all included articles, as well as published review articles of diabetes in New Zealand, 7,16 and global review articles of DR and DM. [17][18][19] All citations obtained from the searches were imported into Endnote (Endnote X8, Thomson Reuters, San Francisco, California), and duplicates removed. The remaining records were imported into Microsoft Excel for screening.…”
Section: Information Sources and Search Strategymentioning
confidence: 99%
“…Of note, serum triglyceride levels were not considered in that study. As discussed in the review by Sabanayagam et al[93] 2016, changes in the circulating levels of lipids are not always associated with DR progression. A recent meta-analysis revealed that the triglycerides, total cholesterol and LDL cholesterol were significantly elevated in persons with diabetic macular edema (DME) when compared to those with DM without DME[94].…”
Section: Dyslipidemia and Development Of Drmentioning
confidence: 99%
“…28 Hyperglycemia has been designated as the most consistent risk factor for DR in type 1 diabetes mellitus. 29 Another point of concern is the management of DR in patients with clinical or sub-clinical cardiovascular disease. Treatment of DR is through laser ablation or use of anti-vascular endothelial growth factor (anti-VEGF) therapy for treating advanced stages of DR.…”
Section: Discussionmentioning
confidence: 99%